Comparison of an alcohol-based hand sanitation product with a traditional chlorhexidine hand scrub technique for hand hygiene preparation in an equine hospital. Issue 5 (3rd September 2017) - Edwards, RA; Riley, CB; Howe, L; Burrows, EA; Riley, KT; Frellstedt, L
Abstract: AIMS: To investigate the efficacy of an alcohol gel-based hand antisepsis protocol compared with a traditional chlorhexidine-based protocol under conditions of routine clinical contamination, and following heavy faecal contamination. METHODS: Twelve adult participants were recruited and on four separate days completed a hand sanitation protocol using a chlorhexidine scrub or an alcohol-based gel, with hands that were grossly clean but contaminated or with faecal contamination. Bacterial samples were obtained from participants' hands before sanitation, immediately after and then 2 hours later. All samples were cultured on blood and MacConkey agar and bacterial colonies counted after 48 hours. RESULTS: for clean contaminated hands, the percentage reduction in bacterial colonies on blood agar immediately after hand sanitation was similar for both protocols (p=0.3), but was greater for the alcohol gel than chlorhexidine after 2 hours (p=0.005). For hands with faecal contamination, the percentage reduction in bacterial colonies on blood agar was similar for both protocols immediately and 2 hours after sanitation (p>0.2), but positive cultures were obtained on blood agar from samples collected after both protocols, for almost all participants. CONCLUSIONS: The results indicate equivalent efficacy of the alcohol-based gel and the pre-surgical chlorhexidine protocol. CLINICAL RELEVANCE: The alcohol-based gel protocol is an effective hand asepsis technique for grossly clean contaminated hands and those following faecal contamination, with comparable efficacy to chlorhexidine based scrub.